2006
DOI: 10.1037/0022-006x.74.5.859
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the validity of self-reported stress-related growth.

Abstract: The purpose of these studies was to assess the validity of self-reported stress-related growth (SRG). In Study 1, individuals with breast cancer (n ϭ 70) generally did not report greater well-being than a matched comparison group (n ϭ 70). In Study 2, there were no significant differences in well-being between undergraduate students who said that something positive had come out of their worst stressor (n ϭ 34) and those who reported no positives (n ϭ 34). In Study 3, specific domains of SRG assessed in undergr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
74
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 65 publications
0
74
0
4
Order By: Relevance
“…As a result, Frazier and Kaler (2006) reported that they found fairly little evidence to validate self-reported growth. Helgeson (2010) also reported little validity when disease-free long-term (10 year) breast cancer survivors' growth reports were compared with their significant others' responses.…”
Section: Issues In Measurement: Validity Of Reported Growthmentioning
confidence: 96%
See 2 more Smart Citations
“…As a result, Frazier and Kaler (2006) reported that they found fairly little evidence to validate self-reported growth. Helgeson (2010) also reported little validity when disease-free long-term (10 year) breast cancer survivors' growth reports were compared with their significant others' responses.…”
Section: Issues In Measurement: Validity Of Reported Growthmentioning
confidence: 96%
“…Because this series of possibilities was raised, several researchers (e.g., Frazier & Kaler, 2006;Helgeson, 2010) have attempted to corroborate self-reported growth in many different ways. As a result, Frazier and Kaler (2006) reported that they found fairly little evidence to validate self-reported growth.…”
Section: Issues In Measurement: Validity Of Reported Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…Cheng et al, 2006;Davis & McKearney, 2003;Frazier et al, 2009;Frazier & Kaler, 2006;Hall, Hobfoll, Canetti, Johnson & Galea, 2009;Hobfoll et al, 2007;McFarland & Buehler, 2012;McFarland & Alvaro, 2000;Wortman, 2004;Yanez, Stanton, Hoyt, Tennen & Lechner, 2011;Zoellner & Maercker, 2006). Most of these researchers do not question the existence of posttraumatic growth but the validity of selfreported posttraumatic growth.…”
Section: Theory Of Reports Of Constructive (Real) and Illusory Posttrmentioning
confidence: 99%
“…In the psychology literature, positive psychological changes triggered by facing challenging adverse life events are referred to as posttraumatic growth (PTG; Tedeschi & Calhoun, 2004). Equally termed as stressrelated growth, perceived benefits, or adversarial growth (Linley & Joseph, 2004), PTG describes the acquisition of more complex coping skills, the development of new perspectives about the self and the world, the improvement of interpersonal relationships, a greater sense of appreciation of life, and changes in life goals as contingent results of the struggle with the aftermath of the stressor (Frazier & Kaler, 2006;Tedeschi, Calhoun, & Cann, 2007). PTG outcomes have been reported in individuals who have experienced a broad range of stressful events, such as cancer (Brunet, McDonough, Hadd, Crocker, & Sabiston, 2010), bereavement (Engelkemeyer & Marwit, 2008), war experience (Kaler et al, 2011), chronic illness (Tran, Wiebe, Fortenberry, Butler, & Berg, 2011), dissolution of romantic relationships (Ty Tashiro & Frazier, 2003), and coming out to others as a sexual minority (Vaughan & Waehler, 2010).…”
Section: Posttraumatic Growthmentioning
confidence: 99%